Influence of geometric imperfections on the ultimate strength of the double bottom of a Suezmax tanker. (15th November 2016) - Estefen, Segen F.; Chujutalli, John H.; Guedes Soares, C.
Highlights: Small-scale models of ship bottom stiffened panels tested under axial compression. Global collapse of the hull girder for two considered cases of geometric imperfection distributions. Influence of local imperfection modes on ship ultimate strength. Abstract: In this work, the influence of initial geometric imperfection modes on the ultimate strength of a ship's hull is studied, with a focus on the buckling behavior of stiffened panels that initiates the structural hull failure. A numerical model of a cargo compartment at the midship of a Suezmax tanker is developed by using the finite element method and by considering both geometric and material nonlinearities. Analyses are conducted under hogging conditions to evaluate the double bottom stiffened panels experiencing axial compression by hull girder bending. Different imperfection modes on the bottom and inner bottom plates are considered in the model. Two cases are studied. In the first one, a half-wave imperfection mode is employed in the longitudinal and transversal directions. In the second case, the imperfection mode coincides with the main natural buckling mode of the plate between the stiffeners. Experimental tests were performed using small-scale models that are representative of the bottom panels, and the results are correlated with those from numerical simulations to define a proper mesh refinement to reproduce the buckling phenomenon. The ultimate strength of the ship hull, in full-scale, employed the same mesh refinement for the bottom panels, assuming the two proposed initial imperfections. The results from the ultimate strength are compared with the reference values for the design bending moment recommended by a classification society.